The poem XI by Alberto Mostajo in the light of the Discourse Analysis - Núñez, Javier (2019)
The aim of this research work was to analyse and interpret Alberto Mostajo (Puno, 1896) poem XI, which is included in his book Canción infinita. The interpretation method used was Discourse Analysis. The following categories of analysis were taken into account: a) identification and characterization of voices; b) characterization of the poem as text; c) determination of the meaning of the poem; d) identification of pragmatic features. The results suggest that the author's context conditioned, to some extent, the production of poem XI. At the enunciative level, Mostajo constructs a subject that speaks in the first grammatical person, whose point of view has subjective, metaphysical and reflexive shades. On a pragmatic level, the enunciator performs the action of informing, with the purpose of generating cognitive and emotional changes in the reader. Likewise, poem XI is a linguistic construction that meets the criteria of textuality. Finally, at the semiotic level, poem XI produces the meaning that life is the way to death, a journey without return. In this process, the subject experiences inner displacement: from reality to unreality, from order to chaos, from lucidity (consciousness) to madness (unconsciousness), from joy to sadness (solitude).